Relatório de Estágio Profissional "Da Vergonha ao Sucesso" - André Emanuel Rosa Alves (2019)
The following document presents a reflective report on the curricular internship throughout the school year in the Pêro Vaz de Caminha School Grouping. The main objective of this internship report, besides describing all the practice throughout the year, such as the activities, the characterization of the classes, the teaching models used, the situations that took place throughout the school year, is the presentation of reflections. on all the topics covered and all the issues that arose during the school year 2018 \ 2019, also reporting all the strategies used to solve the problems that arose and all these situations were a professional addition to the teacher-intern. The Report also includes reflections on all issues, supported by relevant literature for each theme, with articles and works relevant to both the topics addressed in the scope of professional development, as well as the pedagogical and didactic part of the curricular internship. For the part of the theme that I chose to develop throughout the year with the resident class of shame and fear in Physical Education classes. It is also possible to realize that professional practice is much more than just giving classes, it is reflecting on all my actions, which will lead to solutions, but also to new problems, because in addition to giving some answers, will put into question other responses leading to an increasing degree of competence